The effect of peer support on psychological rehabilitation in injured collegiate athletes: the mediating roles of resilience and perceived stress - Liu, Jiawei; Zhao, Jianghong; Wang, Zhenhao (Frontiers in Psychology, 2025)
BackgroundSports injuries are a significant concern for collegiate athletes, often leading to mental issues, including anxiety, depression, and even somatization, due to the combined impact of physical limitations and academic pressure. Peer support interventions (PSI) provide an innovative approach by leveraging shared experiences, emotional support, and coping strategies to facilitate psychological rehabilitation. However, empirical evidence on their efficacy in injured collegiate athletes remains limited. This study aims to assess the efficacy of PSI in facilitating psychological rehabilitation among injured collegiate athletes.MethodA randomized controlled trial was conducted with 51 injured collegiate athletes assigned to either experiment group (PSI, n = 25) or control group (CON, n = 26). The PSI group participated in a 6-week peer support program, while the control group received low-intensity mental health education. Psychological resilience, perceived stress, and mood states were assessed at baseline (T1), 3 weeks (T2), and 6 weeks (T3). Additionally, non-standardized qualitative interviews (n = 10) explored participants’ subjective experiences and the mechanisms underlying PSI effectiveness.ResultsBoth groups showed varying degrees of improvement across all measured indicators compared to baseline, while the PSI group demonstrated higher effect sizes. Compared to the control group, the PSI significantly enhanced psychological resilience (η2p = 0.349) and reduced perceived stress (η2p = 0.572), thereby improving positive moods (e.g., activity and calmness) and reducing negative moods (e.g., anger and depression). Path analysis further revealed that psychological resilience and perceived stress functioned as two parallel mediators through which peer support facilitated improvements in mental health outcomes (βN = −0.864, βP = 0.912, p < 0.001).ConclusionThis study validates PSI as a cost-effective and highly interactive psychological intervention that enhances psychological resilience and alleviates stress in injured collegiate athletes, contributing to overall mental wellbeing. Further larger trials are required to confirm these findings.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=251796, Identifier XJTU1AF2024LSYY-224